2015
DOI: 10.1128/iai.00466-15
|View full text |Cite
|
Sign up to set email alerts
|

EepR Mediates Secreted-Protein Production, Desiccation Survival, and Proliferation in a Corneal Infection Model

Abstract: Serratia marcescens is a soil-and water-derived bacterium that secretes several host-directed factors and causes hospital infections and community-acquired ocular infections. The putative two-component regulatory system composed of EepR and EepS regulates hemolysis and swarming motility through transcriptional control of the swrW gene and pigment production through control of the pigA-pigN operon. Here, we identify and characterize a role for EepR in regulation of exoenzyme production, stress survival, cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 60 publications
3
22
0
Order By: Relevance
“…The transcription factor EepR was recently shown to regulate the prtS and slpB proteases in a positive manner [7]. We tested whether slpE expression was similarly diminished in a Δ eepR strain isogenic to K904 using quantitative RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor EepR was recently shown to regulate the prtS and slpB proteases in a positive manner [7]. We tested whether slpE expression was similarly diminished in a Δ eepR strain isogenic to K904 using quantitative RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that SM6 has one cytotoxic protease compared to K904, which has PrtS, SlpB and SlpE, or that the mutation was in a positive regulator of multiple proteases, as the SM6 protease mutation was never mapped and could have been in a transcriptional regulator. Such regulators may exist, as the EepR gene that positively regulates prtS and slpB expression [7] was postulated to regulate slpE expression. Consistent with this prediction, we observed that slpE expression was highly reduced in an eepR mutant strain.…”
Section: Discussionmentioning
confidence: 99%
“…The tripyrrole red QS controlled pigment, prodigiosin, is synthesized by Serratia through expression of the prodigiosin biosynthetic operon, pigA-N [46,47]. It was found that sitagliptin significantly reduced the expression of pigB gene.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in two different genes that confer major pleiotropic effects on S. marcescens behavior, eepR and gumB, prevented bacterial activation of autophagy. The eepR gene is a transcription factor that is required for wild-type levels bacterial proliferation in a rabbit keratitis model as well as positive regulation of secondary metabolites such as prodigiosin and serratamolide [24,25]. The gumB gene codes for a stress response signal transmitting protein that positively regulates prodigiosin and serratamolide, and is necessary for production of the ShlA, ShlB, and flagellin [20,28].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that secretomes could be heated at 95°C and still induce autophagy [18]. Well-defined S. marcescens strains with deletion mutations in the eepR and gumB genes were tested for loss of autophagy induction because these genes have a conserved and broad impact on S. marcescens biology [20,24,25,28,36]. The EepR and GumB genes regulate expression of multiple secreted factors including heat-stable secondary metabolites such as the biologically active pigment prodigiosin and the hemolytic and antimicrobial biosurfactant serratamolide.…”
Section: S Marcescens Secondary Metabolite Regulators Are Necessary mentioning
confidence: 99%